2018
DOI: 10.1039/c7ob02750h
|View full text |Cite
|
Sign up to set email alerts
|

Iodine–NH4OAc mediated regioselective synthesis of 2-aroyl-3-arylimidazo[1,2-a]pyridines from 1,3-diaryl-prop-2-en-1-ones

Abstract: The present protocol describes an efficient, metal-free regioselective synthesis of 2-aroyl-3-arylimidazo[1,2-a]pyridines from 1,3-diaryl-prop-2-en-1-ones and 2-aminopyridine. The iodine-NHOAc promoted reaction offers a novel route in the synthesis of 2-aroyl-3-arylimidazo[1,2-a]pyridines. This protocol offers significant flexibility in accessing medicinally important 2-aroyl-3-arylimidazo[1,2-a]pyridines with various substitution patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…Based on the control experiments, in situ mass spectrometry analysis of the reaction mixture, and literature precedence, we propose a plausible reaction mechanism in Scheme . Benzamidine hydrochloride 2 a is converted into super nucleophilic benzamidine in the presence of K 2 CO 3 as the base additive.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the control experiments, in situ mass spectrometry analysis of the reaction mixture, and literature precedence, we propose a plausible reaction mechanism in Scheme . Benzamidine hydrochloride 2 a is converted into super nucleophilic benzamidine in the presence of K 2 CO 3 as the base additive.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the significance of imidazoles in medicinal and pharmaceutical chemistry, it is attractive to synthesize the derivatives of these compounds employing readily available precursors. Das has recently reported synthesis of imidazopyridines from 2‐amino pyridines and 1,3‐diaryl‐prop‐2‐en‐1‐one using a stoichiometric amount of iodine and ammonium acetate combination (Scheme a) . Li and Chen reported the synthesis of tetrasubstituted imidazole derivatives using a catalytic amount of iron and iodine combination (Scheme b & c) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, Kapoor et al developed a methodology for the synthesis of 2-aroylimidazo[1,2-a]pyridine derivatives by the oxidative coupling between 2-aminopyridines and chalcones (Scheme 21). [26] They demonstrated that the reaction in presence of 1 equiv. of I 2 and 2 equiv.…”
Section: Synthesis Of 2-aroylimidazo[12-a]pyridinesmentioning
confidence: 99%
“…Ghosh and Hajra obtained furocoumarins via a DABCO‐promoted cyclization transformation of 4‐hydroxycoumarins and nitrostyrenes . Iodine has recently emerged as a promising alternative for many transition metals due to its ability to promote a variety of organic transformations . In this communication, we would like to report a new iodine‐promoted one‐pot cyclization transformation between acetophenones and 4‐hydroxycoumarins to achieve corresponding furocoumarins.…”
Section: Introductionmentioning
confidence: 99%